How planners and stakeholders learn with visualization tools: using learning sciences methods to examine planning processes. Issue 7 (3rd July 2017) - Radinsky, J.; Milz, D.; Zellner, M.; Pudlock, K.; Witek, C.; Hoch, C.; Lyons, L.
Abstract : Planning researchers traditionally conceptualize learning as cognitive changes in individuals. In this tradition, scholars assess learning with pre- and post-measures of understandings or beliefs. While valuable for documenting individual change, such methods leave unexamined the social processes in which planners think, act, and learn in groups, which often involve the use of technical tools. The present interdisciplinary research program used Learning Sciences research methods, including conversation analysis, interaction analysis, and visualization of discourse codes, to understand how tools like agent-based models and geographic information systems mediate learning in planning groups. The objective was to understand how the use of these tools in participatory planning can help stakeholders learn about complex environmental problems, to make more informed judgments about the future. The paper provides three cases that illustrate the capacity of such research methods to provide insights into planning groups' learning processes, and the mediating roles of planning tools.